INTEGRATION OF NOVEL EVENT RECOGNITION USING SPN (SEMANTIC-PROBABILISTIC NETWORK) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Integration of novel event recognition using SPN is describe the events and scenarios pre definedontology is utilized. The Bayesian network is obtained when simple variables and concepts are decomposed into automation conversion. Depend on the concept of ontology, novel approach is introduced. This will calculate the weighted relationship using SPN. By using novel approach gestures are recognized in human gesture recognition system. In this initially multiple layers are given as input. Next these layers are segmented using segmentation. After the layers are segmented data is classified. Once classification is done then event detection is performed. After event detection features are extracted using feature extraction. At last for obtained data, sequence analysis is performed. From results it can observe that precision, recall, average processing time and accuracy will give effective outcome